Physico-mechanical characterization and durability of stabilized compressed earth bricks in the region of Timimoun in southwestern Algeria - Mohammed ABBOU; Abdelaziz SEMCHA; Fatiha KAZI AOUAL (Journal of Materials and Engineering Structures, 2021)
This study primarily aims to determine the physico-mechanical properties and durability of compressed stabilized earth blocks (CSEBs) made from a mixture of clay and crushed sand that meet the recommendations of the French Standard NF P13-901. The first part of this study consists of first identifying the raw materials. An experimental study was then carried out with three compositions of compressed earth bricks of dimensions (29 × 14 × 9 cm3) which were prepared by adding 4%, 6% and 8% of slaked lime. These bricks were prepared using the manually-operated Auram 3000 Earth Block Press to study the effects of slaked lime addition on the physical and mechanical characteristics as well as on the durability of these bricks. In addition, the durability was studied and analyzed in two different curing modes. The experimental study showed that it is possible to use stabilized compressed earth bricks as a building material for an optimal mixture of clay with 70% of crushed and stabilized sand, with a percentage addition of 4%, 6% and 8% of slaked lime.